Silenced rRNA genes are activated and substitute for partially eliminated active homeologs in the recently formed allotetraploid, Tragopogon mirus (Asteraceae) - Dobešová, E; Malinská, H; Matyášek, R; Leitch, A R; Soltis, D E; Soltis, P S; Kovařík, A (Heredity, 2015)
To study the relationship between uniparental rDNA (encoding 18S, 5.8S and 26S ribosomal RNA) silencing (nucleolar dominance) and rRNA gene dosage, we studied a recently emerged (within the last 80 years) allotetraploid Tragopogon mirus (2n=24), formed from the diploid progenitors T. dubius (2n=12, D-genome donor) and T. porrifolius (2n=12, P-genome donor). Here, we used molecular, cytogenetic and genomic approaches to analyse rRNA gene activity in two sibling T. mirus plants (33A and 33B) with widely different rRNA gene dosages. Plant 33B had ~400 rRNA genes at the D-genome locus, which is typical for T. mirus, accounting for ~25% of total rDNA. We observed characteristic expression dominance of T. dubius-origin genes in all organs. Its sister plant 33A harboured a homozygous macrodeletion that reduced the number of T. dubius-origin genes to about 70 copies (~4% of total rDNA). It showed biparental rDNA expression in root, flower and callus, but not in leaf where D-genome rDNA dominance was maintained. There was upregulation of minor rDNA variants in some tissues. The RNA polymerase I promoters of reactivated T. porrifolius-origin rRNA genes showed reduced DNA methylation, mainly at symmetrical CG and CHG nucleotide motifs. We hypothesise that active, decondensed rDNA units are most likely to be deleted via recombination. The silenced homeologs could be used as a 'first reserve' to ameliorate mutational damage and contribute to evolutionary success of polyploids. Deletion and reactivation cycles may lead to bidirectional homogenisation of rRNA arrays in the long term.
Keywords: molekulární evoluce; sekvenční delece; rostlinné geny; Promoter Regions, Genetic; Genes, Plant; Gene Dosage; RNA ribozomální 5.8S; genová dávka; Molecular Sequence Data; RNA ribozomální 18S; geny rRNA; RNA, Ribosomal, 5.8S; promotorové oblasti (genetika); Sequence Deletion; Polyploidy; metylace DNA; Genes, rRNA; Sequence Analysis, DNA; polyploidie; RNA, Ribosomal, 18S; DNA Methylation; umlčování genů; Tragopogon; Nucleolus Organizer Region; sekvenční analýza DNA; Gene Silencing; RNA ribozomální; Evolution, Molecular; organizátor jadérka; molekulární sekvence - údaje; RNA, Ribosomal